Prominence of urinary biomarkers for bladder cancer in the COVID-19 era: From the commercially available to new prospective candidates - Xuan-Mei Piao; Howon Kang; Wun-Jae Kim; Seok Joong Yun (Investigative and Clinical Urology, 2021)
Molecular markers detected in urine may improve our understanding of the evolution of bladder cancer (BCa) and its micro- and macroenvironment. Detection of such markers will identify disease earlier, allow stratification of patients according to risk, and improve prognostication and prediction of outcomes, thereby facilitating targeted therapy. However, current guidelines have yet to embrace such markers for routine management of BCa, and most research studies have focused on urine-based tumor markers. In this review, we summarize known urinary biomarkers for BCa and highlight newly identified molecules. We then discuss the challenges that must be overcome to incorporate these markers into clinical care.